2016
DOI: 10.1017/s095439451600003x
|View full text |Cite
|
Sign up to set email alerts
|

VOT merger in Heritage Korean in Toronto

Abstract: Korean has a typologically unusual three-way laryngeal contrast in voiceless stops among aspirated, lenis, and fortis stops. Seoul Korean is undergoing a female-led sound change in which aspirated stops and lenis stops are merging in voice onset time (VOT) and are better distinguished by the F0 (fundamental frequency) of the following vowel than by their VOT, in younger speakers' speech. This paper compares the VOT pattern of Homeland (Seoul) and Heritage (Toronto) Korean speakers and finds that the same chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 55 publications
5
27
0
Order By: Relevance
“…In some cases, sex based patterns may even be completely reversed. Kang and Nagy (2012) report similar findings in a comparison between Homeland and Toronto Heritage Korean.…”
Section: If We Go Back To the Results Of The Post-hoc Tests For [I] Ssupporting
confidence: 72%
“…In some cases, sex based patterns may even be completely reversed. Kang and Nagy (2012) report similar findings in a comparison between Homeland and Toronto Heritage Korean.…”
Section: If We Go Back To the Results Of The Post-hoc Tests For [I] Ssupporting
confidence: 72%
“…Since Silva (2006), numerous studies have shown that older speakers tend to maintain a three-way VOT categorization (tense< lax<aspirated) whereas younger speakers tend to show a two-way VOT categorization (tense<lax=aspirated) (see also Kang & Guion, 2008 and among others). With respect to the effect of gender on VOT, the VOT merger is more robust in female speakers' speech than in male speakers' speech (Kang & Nagy, 2016;Kim, 2014Kim, , 2017Oh, 2011; and many others). For the effect of dialect on VOT, the merger is more advanced in Seoul dialect than in non-Seoul dialects (Choi, 2002;Kang & Han, 2013;Lee & Jongman, 2012;Oh & Yang, 2013).…”
Section: Vot Variations: a Synchronic Perspectivementioning
confidence: 95%
“…With respect to the role of language contact in sound change, a number of studies have shown that the sound change mainly occurs in Seoul Korean, the standard dialect of Korean, but not in non-Seoul Korean dialects (Choi, 2002;Kim, 2014;Lee & Jongman, 2012). Some studies have shown that the change can also occur to Korean speakers residing abroad, or heritage Korean speakers in Shenyang or Toronto (Jin, 2008;Kang & Guion, 2008;Kang & Nagy, 2016;Oh & Yang, 2013). As for the influence of L2 English on L1 Korean, Kim (2011) reports that the merger phenomenon in the L1 system is more robust for L2 advanced speakers than for L2 beginners because of the amount of L2 experience.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, fundamental frequency (F0) at the onset of the immediately following vowel, which is generally agreed to be the lowest for lax, higher for tense, and highest for aspirated stops, has become the primary cue (Kang, 2014;Kang and Guion, 2006;Kim, Beddor, & Horrocks, 2002;Kim & Stoel-Gammon, 2009;Park & Iverson, 2008;Silva, 2006). Interestingly, this new innovative pattern is also observed among younger Korean speakers in an English-speaking country, Canada (Kang & Nagy, 2016), which is geographically remote from the Korean homeland. Is the same VOT shift also going on in other Korean varieties?…”
Section: Introductionmentioning
confidence: 99%